Evaluation of the lamina cribrosa in patients with multiple sclerosis using enhanced depth imaging optical coherence tomography - Serkan Akkaya; Bekir Kucuk; Ender Sirakaya; Ersin Kasim Ulusoy (Medicine Science, 2018)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system. Optic neuritis (ON) is common clinical manifestation of MS. Spectral domain optical coherence tomography (SD-OCT) has been used as a useful tool to quantify the neuronal damage in the eyes of MS patients. The study aimed to evaluate the lamina cribrosa thickness (LCT) and lamina cribrosa depth (LCD) in patients with MS and their relationship with Expanded Disability Status Scale (EDSS) score. Fifty-two eyes of 26 relapsing-remitting MS patients and 39 eyes of 39 healthy age- and sex- matched participants were evaluated in this prospective, cross-sectional, observational study. There were two MS subgroups: 38 MS eyes without an ON history (MS−ON), and 14 MS eyes with an ON history (MS+ON). The LCT and LCD were measured with SD-OCT. Of the 26 participants with MS, 14 (53.8%) were female and the mean (SD) age was 35.1 (6.2) years; of the 39 healthy controls, 26 (66.7%) were female and the mean (SD) age was 36.7 (8.2) years (P=0.19 for sex and P=0.27 for age). The mean LCT was not significantly different between MS patients and healthy controls (272.66 ± 33.52 μm and 272.58 ± 35.97 μm, respectively, P=0.992). The mean LCD was 325.15 ± 67.07 μm for the MS+ON group, 409.71 ± 93.18 μm for the MS−ON group, and 427.64 ± 91.65 μm for the healthy control group. The LCD was significantly decreased in MS+ON group compared to MS−ON group (P=0.011) and healthy controls (P=0.002). EDSS score was negatively correlated with LCD in MS patients (r= -0.313, P=0.025). This study revealed decreased LCD in MS eyes particularly with optic neuritis, and its relationship with increased disease severity. Additional longitudinal studies are needed to confirm the use of LCD as an imaging biomarker in patients with MS. [Med-Science 2018; 7(4.000): 867-72]